Light‐Induced Nanoscale Deformation in Azobenzene Thin Film Triggers Rapid Intracellular Ca2+ Increase via Mechanosensitive Cation Channels - Heidi Peussa; Chiara Fedele; Huy Tran; Mikael Marttinen; Julia Fadjukov; Elina Mäntylä; Arri Priimägi; Soile Nymark; Teemu O. Ihalainen (Advanced Science, 2023)
Abstract Epithelial cells are in continuous dynamic biochemical and physical interaction with their extracellular environment. Ultimately, this interplay guides fundamental physiological processes. In these interactions, cells generate fast local and global transients of Ca2+ ions, which act as key intracellular messengers. However, the mechanical triggers initiating these responses have remained unclear. Light‐responsive materials offer intriguing possibilities to dynamically modify the physical niche of the cells. Here, a light‐sensitive azobenzene‐based glassy material that can be micropatterned with visible light to undergo spatiotemporally controlled deformations is used. Real‐time monitoring of consequential rapid intracellular Ca2+ signals reveals that the mechanosensitive cation channel Piezo1 has a major role in generating the Ca2+ transients after nanoscale mechanical deformation of the cell culture substrate. Furthermore, the studies indicate that Piezo1 preferably responds to shear deformation at the cell‐material interphase rather than to absolute topographical change of the substrate. Finally, the experimentally verified computational model suggests that Na+ entering alongside Ca2+ through the mechanosensitive cation channels modulates the duration of Ca2+ transients, influencing differently the directly stimulated cells and their neighbors. This highlights the complexity of mechanical signaling in multicellular systems. These results give mechanistic understanding on how cells respond to rapid nanoscale material dynamics and deformations.